English in Economy World: An Overview of English Learning - Ani Setyaningsih; Siwi Karmadi Kurniasih (Universitas Negeri Yogyakarta, 2007)
English is not a language for the English-speaking countries anymore. English has spread worldwide to the countries in the five continents. One of the reasons is economy. People need to acquire English since it is one way to cope with the communication in economy trend. English is needed to process information, analyze, evaluate, experiment, negotiate and collaborate in economy. The awareness of English importance in the globalization era has made people learn this universal language consciously and it brings issues to English language learning especially in non-English-speaking countries.